Amelia Earhart, pioneer in the sky. - Parlin, John.; D'Adamo, Anthony (Champaign, Ill., Garrard Pub. Co., 1962)
A biography of the pilot who became the first woman to fly alone across the Atlantic Ocean and the first woman to receive the Distinguished Flying Cross.
K-3
Keywords: Earhart, Amelia, -- 1897-1937 -- Juvenile literature; Earhart, Amelia, -- 1897-1937.; Air pilots -- United States -- Biography -- Juvenile literature; Air pilots